Characterization of the 18 kDa translocator protein (TSPO) expression in post‐mortem normal and Alzheimer's disease brains. (25th July 2019) - Gui, Yaxing; Marks, Jordan D.; Das, Sudeshna; Hyman, Bradley T.; Serrano‐Pozo, Alberto
Abstract: The 18 kDa translocator protein (TSPO) is a widely used target for microglial PET imaging radioligands, but its expression in post‐mortem normal and diseased human brain is not well described. We aimed at characterizing the TSPO expression in human control (CTRL) and Alzheimer's disease (AD) brains. Specifically, we sought to: (1) define the cell type(s) expressing TSPO; (2) compare tspo mRNA and TSPO levels between AD and CTRL brains; (3) correlate TSPO levels with quantitative neuropathological measures of reactive glia and AD neuropathological changes; and (4) investigate the effects of the TSPO rs6971 SNP on tspo mRNA and TSPO levels, glial responses and AD neuropathological changes. We performed quantitative immunohistochemistry and Western blot in post‐mortem brain samples from CTRL and AD subjects, as well as analysis of publicly available mouse and human brain RNA‐Seq datasets. We found that: (1) TSPO is expressed not just in microglia, but also in astrocytes, endothelial cells and vascular smooth muscle cells; (2) there is substantial overlap of tspo mRNA and TSPO levels between AD and CTRL subjects and in TSPO levels between temporal neocortex and white matter in both groups; (3) TSPO cortical burden does not correlate with the burden of activated microglia or reactive astrocytes, Aβ plaques or neurofibrillary tangles, or the cortical thickness; (4) the TSPO rs6971 SNP does not significantly impact tspo mRNA or TSPO levels, the magnitude of glial responses, the cortical thickness, or the burden of AD neuropathological changes. These results could inform ongoing efforts toward the development of reactive glia‐specific PET radioligands.